The Gender Gap in Public Support for EU Integration in the CEE Countries. A Theoretical Overview - Noe, Brigitta (Intersections. East European Journal of Society and Politics, 2016)
The process of EU integration has been researched in some detail, although while feminist scholars agree that gender is a main organizing principle of social relations, the great majority of the related studies have dealt with integration as a gender-neutral process. The few studies that have examined this problem have applied a gender-centric perspective, mainly focusing on Western European countries, while Central-Eastern European (CEE) relations – which are fairly different due to the post-socialist heritage of the region – remain under-researched. The present paper provides an overview of the relevant scientific literature on the models of support for integration, first highlighting the previously neglected aspect of gender, and later on describing the factors that make its study difficult in a CEE context. The article argues that, in contrast to the assumption made in prevailing approaches to the topic, EU integration is a highly gendered process and may have special characteristics in CEE countries.